2004
DOI: 10.1021/jf0354186
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Coriander Volatile Compounds against Salmonella choleraesuis

Abstract: Aliphatic (2E)-alkenals and alkanals characterized from the fresh leaves of the coriander Coriandrum sativum L. (Umbelliferae) were found to possess bactericidal activity against Salmonella choleraesuis ssp. choleraesuis ATCC 35640. (2E)-Dodecenal (C(12)) was the most effective against this food-borne bacterium with the minimum bactericidal concentration (MBC) of 6.25 microg/mL (34 microM), followed by (2E)-undecenal (C(11)) with an MBC of 12.5 microg/mL (74 microM). The time-kill curve study showed that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
140
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(156 citation statements)
references
References 28 publications
2
140
1
4
Order By: Relevance
“…Hexanal dan 2-hexenal mampu mengurangi kecepatan tumbuh dari populasi mikroba mesotrofik dan psikrotropik pada buah olah minimal di suhu dingin (Patrignani et al 2008). Nonanal dan α,ß-unsaturated aldehid juga menunjukkan penghambatan pada S. aureus dan Salmonella choleraesuis disamping menunjukkan daya antifungal (Kubo et al 2004). Diduga, komponen-komponen asam organik dan aromatik tersebut juga memberikan pengaruh terhadap peningkatan daya hambat dari VCO-BAL dibandingkan dengan VCO kontrol.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…Hexanal dan 2-hexenal mampu mengurangi kecepatan tumbuh dari populasi mikroba mesotrofik dan psikrotropik pada buah olah minimal di suhu dingin (Patrignani et al 2008). Nonanal dan α,ß-unsaturated aldehid juga menunjukkan penghambatan pada S. aureus dan Salmonella choleraesuis disamping menunjukkan daya antifungal (Kubo et al 2004). Diduga, komponen-komponen asam organik dan aromatik tersebut juga memberikan pengaruh terhadap peningkatan daya hambat dari VCO-BAL dibandingkan dengan VCO kontrol.…”
Section: Hasil Dan Pembahasanunclassified
“…Diduga, komponen-komponen asam organik dan aromatik tersebut juga memberikan pengaruh terhadap peningkatan daya hambat dari VCO-BAL dibandingkan dengan VCO kontrol. Efek antibakteri senyawa-senyawa aromatik bersifat lebih lemah dibandingkan asam organik (Kubo et al 2004). Kelarutan asam asetat dan laktat lebih baik pada air dibandingkan minyak dan kadar air dari VCO berkisar pada 0.1-0.5% (Che Man et al 1997).…”
Section: Hasil Dan Pembahasanunclassified
“…A study found both the leaves and seed to contain antioxidants, but the leaves were found to have a stronger effect 6 . Chemicals derived from coriander leaves were found to have antibacterial activity against Salmonella choleraesuis and this activity was found to be caused in part by these chemicals acting as non-ionic surfactants 7 . Coriander has been used as a folk medicine for the relief of anxiety and insomnia in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Coriander is an annual spice and aromatic herb that belongs to the family umbelliferae/Apiaceae (Hedburg and Hedburg, 2003). It is used in culinary (Diederichsen, 1996), medicine (Kubo et al, 2004;Delaquis et al, 2002) and; its green foliage rich in vitamins and other minerals is used in vegetables and salads. Seeds can be used as a spice and contain essential oils rich in linalool (Singh et al, 2005).…”
Section: Introductionmentioning
confidence: 99%